Research on integrated fusion technology of multi-source heterogeneous hybrid information based on Mesh network - ZHANG Weiren, HUANG Xuxing (Zhihui kongzhi yu fangzhen)
According to the practical task of data construction and development, and the characteristics of data integration and application for “wide area multi-ability warfare”, a scheme of wireless intelligent transmission for large data in combat is proposed based on Mesh network technology, real-time transmission of various types of combat data to remote data processing platforms for visual operations and intelligent data storage and analysis, to provide command organizations at all levels, interactive and controllable “science and technology +”“network +” data integration using a new model.